PENGARUH RELAKSASI OTOT PROGRESIF TERHADAP INSOMNIA PADA PENDERITA CONGESTIVE HEART FAILURE (CHF) - Dewi, Sarika '; ', Bayhakki '; ', Misra wati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
The purpose of this study was to determine the effect of progressive muscle relaxation on insomnia in patients with Congestive Heart Failure (CHF).This research desain was a quasi-experimental design with the equivalent control group design approach. The study was conducted at the General Hospital Arifin Achmad to 30 samples 15  for the experimental group and 15 for control group using purposive sampling technique with regard to inclusion criteria. Data were collected using a questionnaire. Data analysis used univariate and bivariate analysis with dependent and independent t-test.The results showed that  progressive muscle  relaxation technique took effect to insomnia with p value = 0.000. The study recommends health workers to teach  progressive muscle relaxation techniques to reduce insomnia in patients with CHF.   Keywords: Congestive heart failure, insomnia, relaxation techniques.